Primer registro de focos de fasciolosis y paramfistomosis en bovinos doble propósito, Gómez Plata, Antioquia, Colombia (2012)
ABSTRACT: Fasciolosis and Paramfistomosis are diseases caused by the trematodes Fasciola hepatica and Paramphistomidae respectively, which affect cattle worldwide and reduce their productivity. Colombia has high prevalence of these fluke, even in coinfection. Northern Antioquia municipalities have 29% of fasciolosis prevalence. In our observations of the Gomez Plata municipality when is develop livestock dual purpose; founded a livers confiscate infected with F. hepatica where of 6.25%, and almost all coming from the village Balsas. OBJETIVE This study proposed to determine fasciolosis and paramphistomosis foci and the prevalence of both parasites in Balsas village cattle. MATERIALS AND METHODS A cross-sectional study was performed, we sampled farms and cattle of the village, and we applied an epidemiological survey in each site. Mollusks and cattle fecal samples were collected. The parasitological diagnosis was made by modified Dennis technique, and mollusks were identified taxonomically by morphology. RESULTS 84 fecal samples were collected, in 13 of the 18 farms the village. A prevalence of 47,6% paramfistómidos and 13,1% Fasciola hepatica were determined. Coinfection was found in 9% of the cattle. Lymnaea columella was collected in two farms, both tested positive for both trematodosis. CONCLUSIONS We determined for the first time in Colombia, confection with fasciolosis and paramfistomosis in dual purpose cattle, and foci of these parasites in the village of Balsas. Key words: Cattle diseases. Fasciola hepatica. Focus. Lymnaea. Paramphistomosis. Prevalence.